Concurrent activity of anammox and denitrifying bacteria in the Black Sea - Kirkpatrick, John B.; Fuchsman, Clara A.; Yakushev, Evgeniy; Staley, James T.; Murray, James W. (Frontiers in Microbiology, 2012)
After the discovery of ANaerobic AMMonium OXidation (anammox) in the Black Sea in 2003, the role of heterotrophic denitrification as the main marine pathway for fixed N loss was questioned. A 3 part, 15 month time series investigating Black Sea nitrite reductase (nirS) mRNA transcripts at a single location was conducted in order to better understand the activity of anammox and denitrifying bacteria. Here we show that both of these groups were active, as well as being concurrent in the lower suboxic zone over this time span. Their distributions, however, were fundamentally different; denitrification expression was much more variable. Depth profiles covering the suboxic zone showed that the four groups of anammox-type sequences were expressed consistently in the lower suboxic zone, and were consistent with anammox 16S rDNA gene profiles. By contrast, denitrifier-type nirS sequence groups were mixed; half of the groups exhibited consistent expression in the lower suboxic zone, while others varied between season and depth. Co-occurrence of both anammox and denitrifier expression was common and ongoing. Both types of transcripts were also found in samples with low concentrations of sulfide ( >2 μM). 6 major groups of denitrifier-type nirS transcripts were identified, making these transcripts more diverse than previous DNA clone libraries. Several groups of denitrifier-type nirS transcripts were closely related to sequences from the Baltic Sea. An increase in denitrifier-type nirS transcript diversity and depth range in October 2007 corresponded to an increase in mixed layer net community productivity as measured by O2/Ar gas ratios, as well as to an increase in N2 concentrations in the upper suboxic zone. Taken together, the variations in expression patterns between anammox and denitrification provide one explanation as to how near instantaneous rate measurements, such as isotope spike experiments, may regularly detect anammox activity but underreport denitrification.